PENGARUH AKTIVITAS FISIK RUMAHAN TERHADAP TEKANAN DARAH PADA IBU RUMAH TANGGA YANG MEMILIKI RIWAYAT HIPERTENSI DI KELURAHAN TITI KUNING - GARBIE SYAHLY AGUNG; AHMAD HANDAYANI (JURNAL ILMIAH KOHESI, 2021)
Based on data from the World Health Organization, it is stated that 972 million or 26.4% of people worldwide havehypertension. This high blood pressure can lead to coronary heart disease, heart failure, and stroke. According to the WorldHealth Organization (WHO), hypertension is a non-communicable disease suffered by people in Indonesia with a fairly highpercentage (57.6%). Physical inactivity can increase the risk of uncontrolled hypertension by increasing stimulation of thesympathetic system and plasma levels of catecholamines which can increase blood pressure. Housewives tend to lackphysical activity or exercise and are only limited in doing physical activities at home, especially with the current pandemicconditions which require people to do activities at home. To determine the relationship of home physical activity to bloodpressure in housewives who have a history of hypertension. This study was conducted using a categorical analytic methodwith a cross-sectional study design from September 2020 to January 2021 in Titi Kuning Village, Medan Johor District,Medan. Based on the results of the analysis, it was found that the most demographic characteristics of the age group werefound at the age of 26-35 years, namely 12 people (40%), the highest blood pressure category was in the 1st-degreehypertension group, namely 15 people (50%), moderate physical activity category being the most found, namely as many as16 people (53.3%) with a value of p = 0.001. There is a significant relationship between home physical activity on bloodpressure in housewives who have a history of hypertension.